Strategije in poslovni modeli spletnih producentov novic v Sloveniji - Sekloča, Peter (Javnost (Ljubljana), 2021)
Until digitalisation got into full swing, news producers had been operating on two-tier markets for advertisers and audiences. Now, the former are leaving, and the latter are not willing to pay for the news, heightening the business risk for digital news media that is increased also by strong domestic and global competition. Due to these changes, commercial media companies have adopted multi-revenue business models that increase the supply of non-media products and services. In this way, audiences are transformed into consumers while the strategy of price leadership prevails in the production of news and audiences. An analysis of interviews with Slovenian media workers is the basis for the explication of the relationships between risks that digitalisation brings about, adequate competitive strategies and suitable business models. Results show that dominant web-based media as well as newspaper publishers are diversifying their product portfolios to fortify the economy of scope and that advertisers are becoming the central stakeholders but that there are no incentives to heighten the use value of news for citizens. Media managers shape the business models according to the expressed demand of advertisers and revenue-powerful marketing departments while paying much less attention to the overall stakeholder structure, which also includes journalists and the public.
Keywords: business models; digital news; information goods; journalism; media economics; novinarstvo; poslovni modeli; risk; spletni portali; spletno komuniciranje; strategies